2022
DOI: 10.1029/2021ja030255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot Protons on the Pitch Angle Scattering of Ring Current Protons by EMIC Waves

Abstract: Via cyclotron resonant interactions, electromagnetic ion cyclotron (EMIC) waves play an important role in the loss of ring current protons. In this study, by calculating the proton bounce‐averaged pitch angle diffusion coefficients using both the cold and hot plasma dispersion relations, we investigate the effects of hot protons on the EMIC wave‐induced scattering loss of ring current protons. Our results show that, for H+ band (He+ band) EMIC waves, inclusion of hot protons results in significant decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 67 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…However, inclusion of hot plasmas can modify the real part dispersion relation of EMIC waves (e.g., Cao et al, 2017b;Chen et al, 2013;Silin et al, 2011;Ni et al, 2018). Zhu et al (2022) suggested that the cold plasma approximation tend to underestimate EMIC wave-induced loss of a few keV to tens of keV protons but overestimate that of higher energy protons. It is thus of importance to include the hot plasma effects when comparing quantitatively the contributions of FLC and EMIC waves to ring current proton scattering.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, inclusion of hot plasmas can modify the real part dispersion relation of EMIC waves (e.g., Cao et al, 2017b;Chen et al, 2013;Silin et al, 2011;Ni et al, 2018). Zhu et al (2022) suggested that the cold plasma approximation tend to underestimate EMIC wave-induced loss of a few keV to tens of keV protons but overestimate that of higher energy protons. It is thus of importance to include the hot plasma effects when comparing quantitatively the contributions of FLC and EMIC waves to ring current proton scattering.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This study improves the current understanding of the relative contributions of scattering by FLC and EMIC waves to the Earth's ring current proton dynamics. In addition to FLC scattering, electromagnetic ion cyclotron (EMIC) waves can cause the scattering loss of ring current protons via cyclotron resonant wave-particle interactions (Cao et al, 2019(Cao et al, , 2020Cornwall et al, 1970;Ma et al, 2019;Summers, 2005;Xiao et al, 2011;Zhu et al, 2022), thus contributing importantly to the storm-time ring current decay (e.g., Kozyra et al, 2013;Shreedevi et al, 2021;Usanova et al, 2010;Yahnin & Yahnina, 2007). Runov et al (2016) suggested that pitch angle scattering by EMIC waves also affects the evolution of pitch angle distribution of the partial ring current ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion cyclotron waves are frequently observed at frequencies below the proton gyro‐frequency in the Earth's magnetosphere and magnetosheath (e.g., Anderson et al., 1994; Gary et al., 1993). These waves induce the rapid loss of both radiation belt electrons (Albert & Bortnik, 2009; Cao, Ni, et al., 2017; Cao, Shprits, et al., 2017; Engebretson et al., 2018; Miyoshi et al., 2008; Ni et al., 2015, 2018; Shprits et al., 2016, 2017; Su et al., 2017; Summers & Thorne, 2003; Yu et al., 2019b, 2020) and ring current protons (Cao et al., 2019, 2020; Cornwall et al., 1970; Ni et al., 2022; Summers, 2005; Summers et al., 2007a, 2007b; Xiao et al., 2012; Zhu et al., 2022) via cyclotron resonant interactions. It has been suggested that ion cyclotron waves at Jupiter account for the scattering loss of energetic protons in Jupiter's magnetosphere (Mauk, 2014; Nénon et al., 2018) and the presence of x‐ray pulsations in Jupiter's high‐latitude polar regions (Yao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…10.1029/2022GL102394 2 of 11 Engebretson et al, 2018;Miyoshi et al, 2008;Ni et al, 2015Ni et al, , 2018Shprits et al, 2016Shprits et al, , 2017Su et al, 2017;Summers & Thorne, 2003;Yu et al, 2019bYu et al, , 2020 and ring current protons (Cao et al, 2019(Cao et al, , 2020Cornwall et al, 1970;Ni et al, 2022;Summers, 2005;Summers et al, 2007aSummers et al, , 2007bXiao et al, 2012;Zhu et al, 2022) via cyclotron resonant interactions. It has been suggested that ion cyclotron waves at Jupiter account for the scattering loss of energetic protons in Jupiter's magnetosphere (Mauk, 2014;Nénon et al, 2018) and the presence of x-ray pulsations in Jupiter's high-latitude polar regions (Yao et al, 2022).…”
mentioning
confidence: 99%